Compressible and Electrically Conducting Fibers for Large‐Area Sensing of Pressures. (29th October 2019) - Leber, Andreas; Page, Alexis Gérald; Yan, Dong; Qu, Yunpeng; Shadman, Shahrzad; Reis, Pedro; Sorin, Fabien
Abstract: Flexible pressure sensors offer a wide application range in health monitoring and human–machine interaction. However, their implementation in functional textiles and wearable electronics is limited because existing devices are usually small, 0D elements, and pressure localization is only achieved through arrays of numerous sensors. Fiber‐based solutions are easier to integrate and electrically address, yet still suffer from limited performance and functionality. An asymmetric cross‐sectional design of compressible multimaterial fibers is demonstrated for the detection, quantification, and localization of kPa‐scale pressures over m 2 ‐size surfaces. The scalable thermal drawing technique is employed to coprocess polymer composite electrodes within a soft thermoplastic elastomer support into long fibers with customizable architectures. Thanks to advanced mechanical analysis, the fiber microstructure can be tailored to respond in a predictable and reversible fashion to different pressure ranges and locations. The functionalization of large, flexible surfaces with the 1D sensors is demonstrated by measuring pressures on a gymnastic mat for the monitoring of body position, posture, and motion. Abstract : Compressible and conducting fibers for the measurement of kPa‐scale pressures over m 2 ‐size surfaces are demonstrated. Pressure quantification and localization on the thermally drawn fibers are achieved through the selective and reversible contacting of composite electrodes within a thermoplastic elastomer support at distinct pressure levels. By functionalizing surfaces with the fibers, pressures are assessed for body position, posture, and motion monitoring.